MENINGKATKAN KEPERCAYAAN DIRI MELALUI BERMAIN PERAN PADA ANAK USIA 4-5 TAHUN DI KELOMPOK BERMAIN PERMATA IBU KECAMATAN KAMPAR UTARA KABUPATEN KAMPAR - Nurfitrianis, Nurfitrianis; Zulirfan, Zulirfan; Risma, Devi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to determine the increase in confidence in children aged 4-5 years through play a role in Playgroup Gem Capital of North Kampar District Kampar regency. This study is kind studies using action research or (PTK) is conducted in two cycles. Each cycle consists of planning, action planning, observation / evaluation and reflection. Subject empirically are children age 4-5 years are numbered 15 children in KB Permata Ibu , The research data obtained through observation and data analysis was done by using quantitative descriptive analysis. The research shows that play a role can improve confidence in children aged 4-5 year. It can be seen from the increase in the average percentage of confidence in the first cycle of 47.27%, which is in the category of less and an increase of 54% in the second cycle be 72.83% which are in both categories. So, playing the role of can improve confidence in children aged 4-5 years in preschool Gem Capital of North Kampar District Kampar regency.Keywords : Confidence, playing Role